Aunt Dimity and the heart of gold [compact disc, unabridged] - Atherton, Nancy (Aunt Dimity, 2019)
Joining friends for an annual holiday bash at Emma Harris' manor that turns into an overnight stay because of stormy weather, Lori Shepherd sets out to unravel a mystery when guest Tilly Trout discovers a hidden compartment filled with a treasure in gold.